Sustainability of Urban Mobility of Campinas City, Brazil - Turra, Christian (European Journal of Sustainable Development, 2019)
In the last decades, urbanization has increased and it has shown to be an irreversible process. The negative impacts of urban growth make to sustainable actions necessary. One of the cities that have national relevance in its economic, social and demographic aspects is Campinas, in the state of Sa?o Paulo, Brazil. The objective of this study was to evaluate the performance of urban mobility and offer sustainable alternatives for the improvement of urban mobility in this city. A quali-quantitative survey was carried out with 234 citizens in Campinas, in three public squares and one municipal park. The results showed that the majority of the interviewed citizens were female, aged between 21 and 30 years old, undergraduate and employed with an income of 1 to 2 minimum wages. Their monthly expense on urban mobility represents, on average, 5% to 10% of the family income. The car was the main means of transportation. The main difficulty in transportation reported was traffic. Most of the interviewed individuals spend 10 to 20 minutes to commute to work or university. Among the main suggestions pointed out by the interviewees for the improvement of urban mobility are newer and more modern buses. Train or subway can be options to diminish the traffic and air pollution and were also suggested by the interviewees. Constant evaluation and monitoring of urban mobility are necessary to understand the real needs of the population and carry out the necessary actions. Keywords: urban mobility; sustainability; Campinas city; vehicles, urban landscape.